2021
DOI: 10.1093/noajnl/vdab021
|View full text |Cite
|
Sign up to set email alerts
|

A Dutch phase III randomized multicenter trial: whole brain radiotherapy versus stereotactic radiotherapy for 4–10 brain metastases

Abstract: Background The clinical value of whole brain radiotherapy (WBRT) for brain metastases (BM) is a matter of debate due to the significant side effects involved. Stereotactic radiosurgery (SRS) is an attractive alternative treatment option that may avoid these side effects and improve local tumor control. We initiated a randomized trial (NCT02353000) to investigate whether quality of life is better preserved after SRS compared with WBRT in patients with multiple brain metastases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Therefore, only 29 out of a planned 230 patients were randomized into groups, of whom 20 patients were included in this QoL analysis. Due to this small study population, no major significant differences could be determined between the two treatment groups' survival and a possible outlier, which we did not found, could possible influence our data (18). In radiation oncology, clinical-trial failure is common.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, only 29 out of a planned 230 patients were randomized into groups, of whom 20 patients were included in this QoL analysis. Due to this small study population, no major significant differences could be determined between the two treatment groups' survival and a possible outlier, which we did not found, could possible influence our data (18). In radiation oncology, clinical-trial failure is common.…”
Section: Discussionmentioning
confidence: 79%
“…Both of these patients had experienced epileptic seizures prior to SRT treatment, and their seizures were controlled with medication. Toxicity among the study participants mainly consisted of hair loss and fatigue among the WBRT group (18). We observed a significant difference in hair loss at 3 months post-treatment between the two study groups, with poorer results for the patients who had been treated with WBRT (P=0.014).…”
Section: Other Qol Measurements Toxicity and Dexamethasone Usementioning
confidence: 74%
See 2 more Smart Citations
“…Recently, the first phase III randomized controlled trial (Dutch Trial) investigating WBRT versus SRS for patients with 4–10 BM suggested that SRS is a valid palliative treatment option for patients with polymetastatic disease for the reduced incidence of toxicity and for the preservation of QoL. Anyway, the trial was closed prematurely, mainly as a result of patients’ and doctors’ preference for SRS, and no definitive results were produced on the non-inferiority of SRS in term of OS and brain failure-free survival ( 106 ).…”
Section: How To Limit Neurocognitive Impairmentmentioning
confidence: 99%